PERLINDUNGAN HUKUM BAGI NOTARIS SELAKU PIHAK PELAPOR SEHUBUNGAN DENGAN PRINSIP MENGENALI PENGGUNA JASA NOTARIS - HADIAWATI TAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Notaris Dr. Henry Sinaga, SH, MKn2.  Notaris Dr. Tony, SH, MKn3.  Notaris Dr. Suprayitno, SH, MKn The research problems are firstly, how the authority of a notary in the principle of recognizing notary service users is; secondly, how the obligations of a notary as the reporting party in relation with the implementation of the principle of recognizing notary service users; and thirdly, the legal protection for a notary as the reporting party concerning his obligation to implement the principle of notary service users. The research employs the theory of legal authority, theory of obligation, and theory of legal protection to answer its problems. The results of the research demonstrate that a notary is obliged to implement the principle of recognizing notary service users, by the time he is having business relationship with his service users.Keywords: Authority of a Notary, Obligation of Reporting, Suspicious Financial Transaction